Risk Based Bank Rating Analysis on Company Reputation and Value (Study on Islamic Commercial Banks in Indonesia) - Wibawati, Roemy Asri Suasti; Fatwa, Nur; Sobari, Nurdin; Rini, Nova (Formosa Journal of Sustainable Research, 2025)
The study investigates the performance of Indonesian Islamic Commercial Banks through a comprehensive analysis encompassing multiple critical dimensions. By examining key performance indicators such as corporate governance, financial profitability, capital structure, and reputation risk, the research provides a holistic evaluation of these financial institutions. The investigation leverages authorized rating agency assessments, specifically from Pefindo, to gauge the banks' stability and market positioning. Additionally, the study integrates the Indonesian Sharia Stock Index (ISSI) as a benchmark, focusing on Sharia-compliant bank stocks to understand their market dynamics. A distinctive aspect of the research is its multifaceted company valuation approach, which analyzes book value, market value, and intrinsic value. This methodology offers nuanced insights into the banks' current performance and future potential within the capital market. The primary findings reveal that accredited agency ratings and ISSI inclusion serve as robust indicators of Islamic banks' operational health. Moreover, the analysis demonstrates a significant correlation between stock prices and the fundamental financial performance of these banking institutions